Scientific American. – 1865. – Vol. 13, № 3 - б/а (New York. Munn @ Company, 1865)
A weekly journal of practical information in art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 13, N 1–16. – New York, 1865. – P. 1–254.
Keywords: July 15, 1865; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::TECHNOLOGY; Research Subject Categories::NATURAL SCIENCES::Chemistry; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; Recent American Patents; Patents; Jackson’s Hominy Mill; On Scientific Experiments in Balloons; Benzol in Canadian Petroleum; Agricultural Machinery; Dummer’s Funnel and Measure Combined; Improved Washing Machine; Buckwalter’s Washing Machine; To Keep Eggs; Foster’s Double-cylinder Revolving Engine; American Annual Cyclopedia; Bickel’s Power-multiplying Machine; Industrial Exhibition in Germany